Understanding the Determinants of Fuel Demand in Costa Rica, 1965-2019: Price, Income, and Registered Vehicles - Pérez Molina, Eduardo (2022)
Fuel demand during the last 50 years in Costa Rica has increased constantly. Do the price of fuels and Gross National Income contribute to explain these trends? This paper explores the existence of causal relations between economic growth, fuel price, and transport demand (represented by fuel consumption and registered vehicles). Vector autoregression (VAR) models were estimated with a time series of data of 1965-2019. Causal relations were found between fuel demand and income, but not with registered vehicles. The effect of price on demand and income were documented, which is important for policy formulation (in particular, possible taxation of fuel demand as a carbon mitigation strategy).